Penerapan Metode Altman Z-Score, Grover Score, Springate dan Zmijewski Untuk Memprediksi Potensi Kebangkrutan - Judi Suharsono; Mutimmah Rustianawati; Alvina Febriani; M Novan Fithrianto; Mufid Andrianata (eCo-Fin, 2025)
This research was conducted to determine the application of the Altman Z-Score, Grover Score, Springate and Zmijewski methods in predicting potential bankruptcy in food and beverage companies listed on the IDX for the 2021-2023 period. The type of research used is descriptive quantitative. Sample selection using purposive sampling method which resulted in 42 samples with 14 companies. The data used is secondary data, namely the company's annual financial statements food and beverage companies for the period 2021-2023. Data analysis is carried out by collecting financial statement data, calculating ratios, classifying company conditions, and comparing the results of the 4 methods. The results state that the Altman z-score method is the best method based on the ability to detect 4 companies that are at risk in the early stages (gray) before entering bankruptcy (dangerous), this can provide time for companies to improve their financial performance. springate method has 1 company that has gone bankrupt. this method only divides into 2 categories without a gray zone so it is less detailed in identifying early stage risks, while the grover score and zmijewski methods show the results of 14 companies in a healthy condition.